A regulating method for reducing nitrogen loss based on enriched ammonia-oxidizing bacteria during composting. (December 2016) - Zhang, Yun; Zhao, Yue; Chen, Yanni; Lu, Qian; Li, Mingxiao; Wang, Xueqin; Wei, Yuquan; Xie, Xinyu; Wei, Zimin
Graphical abstract: Highlights: Inoculation with enriched bacteria reduced ammonia emission and nitrogen loss. Inoculation changed the succession and diversity of bacteria community. Possible mechanism for reducing nitrogen loss was revealed based on RDA. A method for fixing nitrogen and optimizing composting process was proposed. Abstract: In this study, enriched ammonia-oxidizing bacteria (AOB) were acquired by domesticated cultivation, followed by inoculation into the co-composting of rice straw and chicken manure. The effect of inoculation on nitrogen loss, the succession of bacterial community and the correlation between the key bacteria and environmental factors were investigated. The results showed that inoculation could reduce ammonia emission and nitrogen loss by transforming ammonium into nitrite. Inoculation also increased the amount and abundance of bacterial community. Redundancy analysis showed that indigenous and exogenous bacteria in inoculation group, compared with those in control group, were positively correlated with nitrite but negatively correlated with ammonium, demonstrating that the former contributed to the lower ammonia emission and nitrogen loss. Based on these results, the application of enriched AOB was proposed as a new method of resource recycle and improvement of composting technology.